Dividend Policy: Informational Content or Partial Adjustment? - Ang, James S. (The Review of Economics and Statistics, 1975)
IN making dividend decisions, the firm determines the division of earnings between reinvestment and distribution to stockholders. There are two general issues in the area of dividend policy: The first concerns the determinants of the firm's payout ratio (the ratio of dividends to earnings). The second issue concerns the intertemporal change of dividends. The focus of this paper is on the second issue. There are two prevailing views on the behavior of corporate dividend policies over time; the informational content and the partial adjustment hypothesis. In the following sections, both hypotheses are shown leading to empirically equivalent expressions. To avoid this confusion, we suggest an approach that would differentiate between the two hypotheses. Empirical results analyzing dividends behavior of twenty broad industry categories are summarized.